Indispensable amino acid deprivation does not cause rapid amino acid depletion in fish body and this principle has a potential to be used as the new strategy in nutrition - Dabrowski, Konrad; Zhang, Yongfang; Arslan, Murat; Fyhn Terjesen, Bendik (Revista Colombiana de Ciencias Pecuarias, 2016)
Degradation of body proteins occurs not only during fasting but it is a continuous process of renewal of proteins, including those degraded proteosomally immediately after synthesis which apparently accounts for 30% of all newly formed (18), as well as those “storage” proteins that are hydrolyzed at much slower rate by cytoplasmic proteases. If this concept is applied to acute deficiency in indispensable amino acids in food, then such imbalances may in fact become imperfections physiologically overridden by continuous flow of amino acids returned to synthesis sites. Studies conducted in animals have shown that an amino acid imbalanced diet reduced feed intake (10, 16) and growth of animals (5, 8). . In addition, studies have also demonstrated that rats could recover from such deficiency when fed with feed containing the specific IDAA they were lacking (12). . Recently, Hao et al, (2005) argued that mammals recognize dietary IDAA deficiency in the brain‘s anterior cortex that is signaling diet rejection (7). . However, there was no information available on how IDAA deficient diets affect fish feed intake, feed utilization and differences in feed acceptance in a short term (within hours) and during a long period (within several weeks) until recently. We presented evidence that fish may in fact differ from a mammalian model, and a generalization over the anorectic response in the case of lacking IDAA did not apply (3). Amino acid balanced diets in monogastric animals must be composed of various protein sources to provide the right proportion of all IDAA. Compared to fish meal, the major feed protein sources, such as plant proteins and meat and bone meal are deficient in methionine, whereas oilseeds are deficient in lysine. Therefore, these ingredients may not be used as the sole protein source in formulated, high-protein content (45-55%) diets. Under practical farming conditions, feed formulations that include plant proteins may result in disproportionate amounts of IDAA and IDAA deficiencies. IDAA deficient diets affected animals adversely, including depression of food intake and growth, change of feed intake behavior, development of lesions and result in low survival rates (8). Previous studies showed that feed intake of rats decreased significantly after they were fed a threonine deficient diet in comparison to control group (10, 11). The level of plasma histidine and threonine decreased rapidly after ingesting histidine or threonine deficient diets respectively, while the level of plasma total IDAA other than histidine and threonine increased significantly. There was no significant change in the plasma dispensable amino acid (DAA) concentrations after rats consumed histidine or threonine deficient diets. Liver and muscle histidine or threonine concentrations decreased after rats were fed histidine or threonine imbalanced diets (14). Feurte et al, (1999) also reported that plasma threonine concentrations significantly decreased between 30 to 60 minutes after rats ingested a threonine devoid diet (4). The mechanism of interdependence of behavioral response (food rejection) and physiological indicators (concentration of IDAA in tissue) is being addressed systematically in mammals. . Studies showed that a threonine-imbalanced diet significantly decreased threonine concentrations in the anterior piriform cortex (APC) of the brain (5). . This correlated with rats rapidly rejecting IDAA deficient diet i.e. within 15 min after ingestion of threonine-imbalanced diet. Recent studies by Koehnle et al (2003) confirmed that rats recognized threonine deficient diet within the first meal and reduced the first meal duration and rejected the threonine deficient diet within 12-16 min (9). . It has been long recognized, however, that animals as ancient as spiders (6) optimize proportions of IDAA in their diets by adapting specific strategy of nutritional polyphagy. By diversification of prey (protein and amino acid composition), predatory insects arrive at selecting nutrients not only by quantity but also most importantly by quality (13). Weekes et al (2006) suggested an alternative method of induced amino acid imbalance in mammals by abomasal infusion of free amino acid solution lacking one or more indispensable amino acids (20). This is the first attempt to our knowledge that defined response in blood amino acid following prolonged deficiency in healthy animal. However, using fish model may prove to provide enormous advantage in respect to opportunity to follow the dietary impact on the “whole animal level”, whole body free amino acid concentrations.